Mapping the Transformative Effects of Artificial Intelligence on Journalistic Practices - Aziz, Syamsuddin (Komunikator, 2025)
This study examines the impact of artificial intelligence (AI) on journalism by evaluating the advantages, disadvantages, and implications of AI adoption in news production and reporting. Through a scholarly discourse, the study explores how AI technologies are transforming journalistic practices by influencing content creation and news delivery. Using a meta-analytic method to analyze data from independent studies on AI adoption in media journalism, the study assesses the potential benefits of AI, such as improved efficiency and enhanced news accuracy. At the same time, it highlights challenges, including ethical concerns, potential biases, and the evolving role of journalists within technology-driven industries. By examining both the positive and negative effects of AI, this study provides understanding of the complex relationship between AI and media journalism. The findings offer valuable insights for media professionals, researchers, and policymakers involved in shaping the future of news production and distribution.